Association between smoking at diagnosis and cause‐specific survival in patients with rectal cancer: Results from a population‐based analysis of 10, 794 cases. Issue 13 (15th March 2017) - Sharp, Linda; McDevitt, Joseph; Brown, Christopher; Carsin, Anne‐Elie; Comber, Harry
Abstract : Background: Currently, the 5‐year survival rate for rectal cancer remains at <60%. The identification of potentially modifiable prognostic factors would be of considerable public health importance. A few studies have suggested associations between smoking and survival in rectal cancer; however, the evidence is inconsistent, and most of these studies were relatively small. In a large population‐based cohort study, we investigated whether smoking at diagnosis is an independent prognostic factor for cancer‐specific survival in rectal cancer and whether the association varies by sex, age, or treatment. Methods: Rectal cancers (ICD10 C19‐20) diagnosed between 1994 and 2012 were abstracted from the National Cancer Registry Ireland and classified by smoking status at diagnosis. Follow‐up was for 5 years or until December 31, 2012. Multivariable Cox proportional hazards models were used to compare cancer‐specific death rates in current smokers, ex‐smokers, and never smokers. Subgroup analyses by age at diagnosis, sex, and treatment were conducted. Results: A total of 10, 794 rectal cancers were diagnosed. At diagnosis, 25% were current smokers, 24% were ex‐smokers, and 51% were never smokers. Compared with never smokers, current smokers had a significantly greater rate of death from cancer (multivariable hazard ratio [HR], 1.15; 95% confidence interval [CI], 1.06‐1.24), but ex‐smokers did not (HR, 1.02; 95% CI, 0.94‐1.11). The association was slightly stronger in men (current versus never smokers: HR = 1.13, 95% CI, 1.02‐1.24) than females (HR, 1.05; 95% CI, 0.90‐1.23), but the test for interaction was not significant ( P = .75). The effect of smoking was not modified by age or receipt of tumor‐directed surgery, radiotherapy, or chemotherapy. Conclusions: Rectal cancer patients who smoke at diagnosis have a statistically significant increased cancer death rate. Elucidation of the underlying mechanisms is urgently required. Cancer 2017;123:2543–50. © 2017 American Cancer Society . Abstract : Compared with never smokers, current smokers at diagnosis have a significantly increased rate of death from cancer. The effect of current smoking is not modified by age or receipt of tumor‐directed surgery, radiotherapy, or chemotherapy, but is slightly stronger in men than women.